A phase 1 proof-of-concept study evaluating safety, tolerability, and biological marker responses with combination therapy of CTLA4-Ig and interleukin-2 in amyotrophic lateral sclerosis - Thonhoff, Jason R.; Beers, David R.; Zhao, Weihua; Faridar, Alireza; Thome, Aaron; Wen, Shixiang; Zhang, Aijun; Wang, Jinghong; Appel, Stanley H. (Frontiers in Neurology, 2024)
Objective To determine whether a combination therapy with abatacept (CTLA4-Ig) and interleukin-2 (IL-2) is safe and suppresses markers of oxidative stress, inflammation, and degeneration in ALS. Methods In this open-label study, four participants with ALS received subcutaneous injections of low dose IL-2 (1x106 IU/injection/day) for 5 consecutive days every 2 weeks and one subcutaneous injection of CTLA4-Ig (125 mg/mL/injection) every 2 weeks coinciding with the first IL-2 injection of each treatment cycle. Participants received a total of 24 treatment cycles during the first 48 weeks in this 56-week study. They were closely monitored for treatment-emergent adverse events (TEAEs) and disease progression with the ALSFRS-R. Phenotypic changes within T cell populations and serum biological markers of oxidative stress (4-hydroxynonenal [4-HNE] and oxidized-LDL [ox-LDL]), inflammation (IL-18) and structural neuronal degeneration (neurofilament light chain [Nf-L]) were assessed longitudinally. Results CTLA4-Ig/IL-2 therapy was safe and well-tolerated in all 4 participants over the 56-week study. During the first 24 weeks, the average rate of change in the ALSFRS-R was +0.04 points/month. Over the 48-week treatment period, the average rate of change was -0.13 points/month with one participant improving by 0.9 points/month while the other three participants experienced an average decrease of -0.47 points/month, which is slower than the average -1.1 points/month prior to initiation of therapy. Treg suppressive function and numbers increased during treatment. Responses in the biological markers during the first 16 weeks coincided with minimal clinical progression. Mean levels of 4-HNE decreased by 30%, ox-LDL decreased by 19%, IL-18 decreased by 23%, and Nf-L remained the same, on average, in all 4 participants. Oxidized-LDL levels decreased in all 4 participants, 4-HNE and IL-18 levels decreased in 3 out of 4 participants, and Nf-L decreased in 2 out of 4 participants. Conclusions The combination therapy of CTLA4-Ig and IL-2 in ALS is safe and well-tolerated with promising results of clinical efficacy and suppression of biomarkers of oxidative stress, neuroinflammation and neuronal degeneration. In this open-label study, the efficacy as measured by the ALSFRS-R and corresponding biomarkers suggests the therapeutic potential of this treatment and warrants further study in a phase 2 double-blind, placebo-controlled trial.